Key success factors for lean six sigma implementation on Light Rail Transit Station construction project - Ulfa Soraya; Albert Eddy Husin; Bernadette Detty Kussumardianadewi; I Putu Indra Prabawa (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
Transportation is essentially designed to meet the requirements of the movement or movement of a person or an item from one place to another. Transportation has an important role and strategy in achieving goals, including recognizing that transportation is a method of facilitating the wheels of the economy and strengthening unity and integrity in national development. Transportation has an important role and strategy in achieving goals, including recognizing that transportation is a method of facilitating the wheels of the economy and strengthening unity and integrity in national development. In the implementation of the LRT Station construction project, good the timeliness, cost, and quality of a project's overall completion are all influenced by scheduling and quality control. Project delays are common in the process of implementing construction projects. This as a result, the quality is low and does not meet technical criteria. At long last, it caused a project's failure. This study analyzes the key success factor for lean six sigma implementation on Light Rail Transit Station Construction Project. The conclusion of this study is that there is a significant key success factor for lean six sigma implementation on Light Rail Transit Station Construction Project. Based on the outcomes, of the study, ten (10) factors that affect cost performance using Lean Six Sigma include: cost reduction, evaluating quality, ceiling, productivity, waste management, lack of leadership understanding of the project, drawing, design changes, defect rate in work process, variability reduction. The control phase is carried out by the coordinator each division to reduce or eliminate errors in construction application. Control work is carried out regularly and in an organized manner. Transportasi pada hakikatnya dimaksudkan untuk memenuhi kebutuhan memindahkan atau memindahkan seseorang atau benda dari satu tempat ke tempat lain. Transportasi memiliki peran dan strategi penting untuk mencapai tujuan, termasuk dalam pembangunan negara. Dalam pelaksanaan proyek pembangunan Stasiun LRT, baik ketepatan waktu, biaya, dan kualitas penyelesaian suatu proyek secara keseluruhan dipengaruhi oleh penjadwalan dan pengendalian mutu. Keterlambatan proyek sering terjadi dalam proses pelaksanaan proyek konstruksi. Akibatnya, kualitasnya rendah dan tidak memenuhi kriteria teknis. Akhirnya, itu menyebabkan kerugian proyek. Studi ini menganalisis faktor kunci sukses dalam proyek Lean Six Sigma di LRT. Kesimpulan dari penelitian ini adalah terdapat key success factor yang signifikan dari Lean Six Sigma pada stasiun LRT. Hasil penelitian mengungkapkan 10 faktor mempengaruhi kinerja biaya Lean Six Sigma meliputi: pengurangan biaya, evaluasi kualitas, plafon, produktivitas, pengelolaan limbah, Kurangnya pemahaman kepemimpinan proyek, gambar, perubahan desain, tingkat cacat dalam proses kerja, dan pengurangan variabilitas. Tahap pengendalian dilakukan oleh koordinator masing-masing divisi untuk mengurangi atau menghilangkan kesalahan dalam aplikasi konstruksi. Pekerjaan pengendalian dilakukan secara teratur dan terorganisir.